Anal and dry sex in commercial sex work, and relation to risk for sexually transmitted infections and HIV in Meru, Kenya. Issue 5 (21st June 2006) - Schwandt, M; Morris, C; Ferguson, A; Ngugi, E; Moses, S
Abstract : Objective: To examine the practices of anal intercourse and dry sex within a cohort of female sex workers (FSWs) in Kenya, focusing on the prevalence and perceived risk of the practices, demographic and behavioural correlates, and association with sexually transmitted infections (STI). Methods: A survey was conducted among FSWs in Meru, Kenya, with 147 participants randomly sampled from an existing cohort of self identified FSWs. Results: 40.8% of participants reported ever practising anal intercourse and 36.1% reported ever practising dry sex. Although the majority of women surveyed believed anal intercourse and dry sex to be high risk practices for HIV infection compared with vaginal sex, about one third of women reported never or rarely using condoms during anal intercourse, and about 20% never or rarely using condoms during dry sex. Reported consistent condom use was lower with both of these practices than with penile-vaginal intercourse. Anal intercourse was associated with experience of recent forced sexual intercourse, while dry sex was not. Anal intercourse was almost always initiated by clients, whereas dry sex was likely to be initiated by the women themselves. Sex workers reported charging higher fees for both practices than for vaginal intercourse. Both practices were associated with reported symptoms and diagnoses of STI. Conclusions: Both anal intercourse and dry sex were common in this sample, and although perceived as high risk practices, were not adequately protected with condom use. Education and other interventions regarding these high risk sexual behaviours need to be translated into safer practices, particularly consistent condom use, even in the face of financial vulnerability.